BENTUK DAN EKISISTENSI LUDRUK ARMADA PADA MASA PANDEMI COVID-19 - Fitri, Ninda Puspita; Abdillah, Autar (APRON Jurnal Pemikiran Seni Pertunjukan, 2021)
ABSTRAK BENTUK dan EKSISTENSI LUDRUK ARMADA MALANG PADA MASA PANDEMI COVID-19 Kata Kunci : Eksistensi, Ludruk Armada, Pandemi Ludruk Armada merupakan salah satu Ludruk dari Dampit Kabupaten Malang, biasa dikenal sebagai ludruk percontohan, dimana karya-karya yang dihasilkan dari Ludruk Armada Malang ini banyak diminati oleh masyarakat bahkan kalangan muda-mudi tertarik oleh karya-karya Ludruk Armada. Pandemi Covid-19 membuat Ludruk Armada mengalami vakum untuk beberapa waktu. Hal ini membuat proses kreatif dari Ludruk Armada menjadi terdampak akan adanya Pandemi ini. Permasalahan yang dikaji dari penelitian ini adalah 1) Bagaimana Eksistensi Ludruk Armada Malang Saat Pandemi Covid-19? dan 2) Bagaimana Bentuk Pertunjukan Ludruk Armada Malang Sebelum adanya Pandemi Covid-19?. Metode penelitian yang digunakan adalah metode kualitatif, mendiskripsikan informasi dengan menggunakan teknik pengumpulan data dengan observasi, wawancara dan dokumen. Sumber data didapatkan melalui wawancara langsung dan observasi di dukung melalui data pustaka dan dokumentasi pertunjukan. Hasil dari penelitian menunjukkan bahwa Bentuk dan Eksistensi Ludruk Armada Malang, saat terjadinya pandemi mengalami hambatan dari segi pertunjukan, dan juga ekistensi sebelum pandemi memiliki ciri khas. Ludruk Armada mengalami Vakum untuk sementara waktu, namun Ludruk Armada masih berusaha menunjukkan ekisistensi mereka. Meskipun dengan adanya pandemi, namun Ludruk Armada berusaha menunjukkan eksistensi dengan ide kreatif. ABSTRACT The Form and Existence of Ludruk Fleet Malang During the Covid-19 Pandemic Keywords : Existence, Show Form, Ludruk Armada, covid-19 Ludruk Armada is one of the original Ludruk from Dampit Malang, which is commonly known as a pilot ludruk. Some works that produced from Ludruk Armada Malang are interested for all people, even young people and also the actors who attracted by the creation of Ludruk Armada. The emergence of Covid-19 has affected Ludruk Armada, especially disrupted all of Ludruk Armada's artistic activities. Ludruk Armada is a very popular Ludruk in East Java. It existence recognized by the wider community as one of the original traditional theaters of East Java which has produced many works from Ludruk Armada. The Covid-19 pandemic has left Ludruk Armada in a vacuum for a long time. This make the creativity process of Ludruk Armada affected by this Pandemic. Of course, this covid-19 pandemic greatly affects all aspects of Ludruk Armada because Ludruk's art is a Ludruk activity that requires a lot of people and it has the potential to create a crowd, so Ludruk Armada's performance is temporarily suspended. The problems that will be studied from this research are as follows: 1) How is the existence of Ludruk Armada Malang during the Covid-19 Pandemic? and 2) What was the form of the Ludruk Armada's Show Before the Covid-19 Pandemic?. The research method used by the researcher is a qualitative method which the researchers describe information using data collection techniques, namely by observation, interviews and documentation. Sources of data obtained through direct interviews with resource persons and also observations supported through library data and show documentation. The interview was conducted with the leader of the Ludruk Armada, Mr. Djarot Mustadjab. The author also uses source and technique triangulation to test the validity and correctness of the research conducted. The results of the research show that the form and existence of Ludruk Armada Malang, during a pandemic, the conditions of the Ludruk Armada creative process experienced obstacles in terms of performances that were impacted by canceled flight hours, and also Ludruk Armada Malang's existence before the pandemic which was felt by the surrounding community was Ludruk who have their own characteristics and have their own interesting side in their shows, because this pandemic has affected all their artistic activities. This pandemic also made Ludruk Armada experiences are temporary vacuum, but Ludruk Armada is still trying to show their existence. Despite the pandemic, Ludruk Armada is trying to show its existence with their creative ideas.